Navigating Javanese Womanhood in the Digital Age: Perspectives from Digital Natives and Immigrants - Lailisna, Novi Nur; Bashori, Bashori; Budiarti, Meliza (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
Technological development has significantly changed human social life, especially online social media. In Indonesia, device-based social media users reached 191.4 million in January 2022. This number is still being reduced to several types of social media widely used in Indonesia, such as YouTube, Facebook and Instagram, based on Data Reportal Research in February 2022. Female social media users could be said to be active on some social media sites. Consumption of content on social media often makes a spectacle a guide for women. Several perspectives on Javanese women, such as sumur-dapur-kasur, macak-masak-manak, swargo nunut, neroko katut, and Konco Wingking, have a positive philosophical meaning by building perceptions through social media. Therefore, this research explores the perspectives and experiences of Javanese women concerning their participation in the digital space. Using the ethnographic approach, a qualitative research strategy, the study involves in-depth observation, active engagement, and interpersonal interactions within a specific cultural group or community. The result of this research is the perspective of more modern Javanese women in a positive perspective and women themselves. In essence, all perspectives on the philosophical values of Javanese women have shifted, including in practice. Javanese women who open themselves to social media can develop their potential with all these perspectives because the opportunity to become more 'modern' lies in the woman's decision.